Positive psychology as social change - Biswas-Diener, Robert (Springer eBooks., 2011)
In recent times there has been growing interest in positive psychology. This is evidenced by the swell in positive psychology graduate programs, undergraduate courses, journals related to the topic, popular book titles on the topic and scholarly publications. Within the positive psychology community there has been an increased emphasis on the socially beneficial side of positive psychological science. At the First World Congress of the International Positive Psychology Association there was a major push to look at positive psychology as a social change mechanism. This volume will bring together thoughts of leaders in positive psychology from 8 countries to capitalize on the push toward social change and flourishing. By releasing this title at a critical time Springer has the opportunity to help frame the agenda for positive psychology as a force for social change. This seminal work is meant for anyone interested in happiness, strengths, flourishing or positive institutions It introduces Positive Psychology as an unapplied science that can be used to create positive social transformation and enabling institutions. This is a must-have title for academics, especially psychologists, sociologists, economists, and professionals working in the field of Positive Psychology and Well-Being.